2007
DOI: 10.1124/dmd.106.013763
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile of a Peptide-Conjugated Chlorin-Type Photosensitizer Targeting Neuropilin-1: An in Vivo and in Vitro Study

Abstract: ABSTRACT:Because angiogenic endothelial cells of the tumor vasculature represent an interesting target to potentiate the antivascular effect of photodynamic therapy, we recently described the conjugation of a photosensitizer [5-(4-carboxyphenyl)-10,15,20-triphenylchlorin (TPC)], via a spacer [6-aminohexanoic acid (Ahx)], to a vascular endothelial growth factor receptor-specific heptapeptide [H-AlaThr-Trp-Leu-Pro-Pro-Arg-OH (ATWLPPR)] and showed that TPCAhx-ATWLPPR binds to neuropilin-1. Because peptides often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…In practice, the four factors usually considered are the administered PS dose, the time interval between PS administration and light irradiation (drug-light interval [DLI]), the light fluence, and the light fluence rate (12). In our approach, to limit the number of experiments to be carried out, a DLI of 4 hours was selected, corresponding to relevant PS levels in plasma and tumor, low PS levels in skin, and low degradation of the peptidic moiety (13,14). Fixing this parameter, determination of the optimal PDT dosimetry can be expressed as the optimal choice of the three remaining factors (PS dose, light fluence, and fluence rate), i.e., the selection of values leading to an optimal PDT response.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the four factors usually considered are the administered PS dose, the time interval between PS administration and light irradiation (drug-light interval [DLI]), the light fluence, and the light fluence rate (12). In our approach, to limit the number of experiments to be carried out, a DLI of 4 hours was selected, corresponding to relevant PS levels in plasma and tumor, low PS levels in skin, and low degradation of the peptidic moiety (13,14). Fixing this parameter, determination of the optimal PDT dosimetry can be expressed as the optimal choice of the three remaining factors (PS dose, light fluence, and fluence rate), i.e., the selection of values leading to an optimal PDT response.…”
Section: Introductionmentioning
confidence: 99%
“…Although increased uptake of photosensitizer by tumor tissue was solely attributable to the PEG moiety, conjugation to APRPG appeared necessary to suppress tumor growth efficiently. For the first time, we propose to characterize the vascular effect of PDT using a peptide-conjugated photosensitizer targeting NRP-1 (19). As a DLI of 4 h, corresponded to the highest incorporation of TPC-Ahx-ATWLPPR in endothelial cells lining the vessels, has been chosen (17), and since our molecular marker is mainly over expressed by angiogenic vascular endothelial cells (33), the supposed initiating event would be a morphological and functional alteration of endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…TPC was purchased from Frontier Scientific (Logan, UT). TPC-Ahx-ATWLPPR was synthesized and purified as described previously (15,19). Stock solutions in dimethylsulfoxide (2 mM) were used.…”
Section: Photosensitizermentioning
confidence: 99%
“…Our study demonstrated that TPC-Ahx-ATWLPPR accumulated up to 25-fold more in human umbilical vein endothelial cells (HUVEC) than free TPC over a 24 hours period. The accumulation of the conjugated photosensitizer was related to NRP-1-dependent mechanisms but also to non-specific mechanisms (Thomas et al, 2008, Tirand et al, 2007. In vivo biodistribution studies in nude mice xenografted with U87 human malignant glioma cells revealed significant tumour level to normal ratios as early as 1 hour after intravenous injection of TPC-Ahx-ATWLPPR.…”
Section: Vascular Endothelial Growth Factor (Vegf) Receptorsmentioning
confidence: 99%